THE EFFECTIVENESS OF PICTURE POCKET MEDIA IN MULTIPLICATION OF TWO NUMBER IN MATHEMATICS SUBJECTS FOR SECOND GRADE STUDENTS OF SD N 14 RANAH PESISIR - Lili Rismaini; Dewi Devita (Lembaga Penelitian dan Pengabdian Kepada Masyarakat STKIP Ahlussunnah, 2023)
This research is motivated by the fact that learning is still teacher-centered. The rapid development of information technology in recent years has changed the paradigm of society in seeking and obtaining information. This technological advancement has also influenced instructional media. Teachers typically use print learning media. This study aims to produce an effective learning media called